VLTI-GRAVITY measurements of cool evolved stars: I. Variable photosphere and extended atmosphere of the Mira star R Peg - Wittkowski, Markus; Rau, G.; Chiavassa, A.; Höfner, S.; Scholz, Michael; Wood, P. R.; Wit, W. J. de; Eisenhauer, F.; Haubois, X.; Paumard, T. (Astronomy and astrophysics, 2018)
Dynamic model atmospheres of Mira stars predict variabilities in the photospheric radius and in atmospheric molecular layers which are not yet strongly constrained by observations. Here we measure the variability of the oxygen-rich Mira star R Peg in near-continuum and molecular bands.